Road Traffic Rules Violators' Monitoring System - MOHD KHALILI, MUHD HAFIZ (Universiti Teknologi Petronas, 2004)
This purpose of this system is to catch vehicle, which breaks the red traffic signal by sending the unique characters (e.g. vehicle's registration number) to the database and keep the record for future action. The main objective of this project is to transmit alphanumeric characters through RF medium and display the characters on the LCD matrix at the receiver. The system is using digital RF transmitter and receiver integrated with 16F84A PIC micro controller for the ASCII code conversion, data encoding and decoding task. Thus, the next objective is to develop the programming code for the 16F84A to perform all these tasks. In the project, the assembly language is used to develop the programming code. The VMS operates only when the traffic signal is red. In this project, a switch is used to trigger the transmitter in the vehicle at that particular time. The switch is only working under certain state condition (RED light is ON). In the future and practical used, the switch can be replaced with a Hall sensor. The hall sensor detects the magnetic flux introduced by the electromagnet, which is installed under the road surface. The first section of the report will tell about the introduction of background of the project, the concept ofRTRVMS, problem statement, objectives and scopes of study. The second section of the report is literature review of the components used in the system. The third section will be the methodology and project work including the project development. The forth section! is the project Findings and discussion throughout this semester and also the problem facing. This simple system can be one of the solutions to control the road traffic violent in the future.